(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The economic role comes in the ahead of the roles of taxes (after the financial role, which is the basic objective for the tax), because the importance of that role, which can play in achieving economic stability, stimulate growth, and attract foreign and domestic investment. But the tax has not led its economic role in Iraq, in terms of the low average ratio of tax revenue to the level of private consumer spending of 2.62% during the period (2003-2012), and the low average elasticity coefficient of ratio of the change in private consumer spending to the percentage change in tax revenue during the same period to 0.31, and the average of tariff wall reached 0.79% of total imports (consumption + investment) and 16.14% of food commodities during the period (2003-2012).It is assumed that Iraq is an agricultural country, while in the process of attracting the investments, the tax did not contribute to the promotion of domestic or foreign investment, and did not increase the effectiveness of the private sector, since this depends on the availability of attractive investment climate factors in this area more than tax breaks.